Internalization of Social Values in the Village Clean Tradition in Javanese Communities in the Lama Village of Sei Lepan Sub-District, Langkat District - Novi Kartika Sari; Eka Darliana; Deni Hartanto (JURNAL PENDIDIKAN IPS, 2024)
Internalization refers to the process of instilling certain values, which takes place in three stages: transformation, transaction, and trans-internalization. In the case of the clean village tradition in the Old Village, this process occurs during the month of Syuro/Muharram. The aim of this research is to examine the transformation of social values within the clean village tradition in the Old Village Javanese community, the transaction of these values, and the internalization of these values in the community. The research uses a descriptive qualitative approach, with purposive sampling for informants. Data collection methods include interviews, observations, and documentation, while data analysis follows the approach of Miles, Huberman, and Saldana. The results of the research reveal that the transformation of social values within the community of Lama Village, Sei Lepan District, generates positive values, particularly from a religious standpoint, communicated through the clean village tradition. These teachings encourage individuals to live cautiously, avoid violating Allah's religious laws, and maintain a strong sense of faith. The transaction of social values during the clean village ritual enhances the community's faith, tolerance, understanding of almsgiving, concern for the environment, respect for elders, and ability to cleanse negative traits from the heart. The trans-internalization process has become ingrained in the daily lives of the Lama Village community, with social and religious values actively practiced. Deliberation to achieve mutual consensus and the practice of helping and cooperating in times of need remain highly valued in Lama Village, Sei Lepan District.